104 Silent multilevel vertebral fractures in a severe case of glycine receptor antibody-positive progressive encephalomyelitis with rigidity and myoclonus (PERM). (29th July 2019) - Min, Myintzu; Liu, Han; Silberstein, Paul
Abstract : Introduction: Autoimmune encephalitides are a heterogenous and potentially devastating group of disorders. Antibodies to glycine receptor (GlyR) are rare and increasingly reported in patients with progressive encephalomyelitis with rigidity and myoclonus (PERM). PERM patients develop early brainstem and autonomic dysfunction, and if untreated, can be fatal. We aim to discuss the complications and treatments in this PERM case and review the literature on management of PERM. Methods: We report a case of PERM currently undergoing treatment in our hospital. Results: Mr GT is a 46-year-old male who presented with a prodromal phase of altered sensation and acute cerebellar signs. He rapidly deteriorated with bulbar dysfunction and developed generalised muscle rigidity and hyperreflexia. Infective work-up, cerebrospinal fluid analysis, magnetic resonance imaging of brain and spine were initially normal. He was started on first line immunosuppressants for a clinical diagnosis of autoimmune encephalitis. Despite sedation in intensive care, generalised myoclonus and truncal extensor spasms were severe and presented on-going management difficulties. A computed tomography scan of his abdomen to exclude malignancy revealed incidental findings of vertebral fractures at multiple thoracic and lumbar levels. He was subsequently administered rituximab and demonstrated some signs of recovery. GlyR antibody positive results from Oxford University Hospital consequently confirmed his diagnosis. Conclusion: This is the fourth reported GlyR antibody-positive PERM case in Australia and the first description to our knowledge with intractable rigidity and myoclonus leading to vertebral fractures. Awareness and screening for this complication may assist in management of patients with PERM.